Understanding the Impact of ODI on the Interpersonal Skills of the Managers and its Effect on the Subordinates’ Role Commitment - Luesukprasert, Sinchai; Preudhikulpradab, Ph.D., Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
Continuous growth and expansion of a business can lead to various percussions as the organization grows quickly in its size while the ways people interact and communicate remains the same. This paper aims to explore the impact of ODI on the interpersonal skill of managers and its effect on the role commitment of their subordinates within that organization. This study involves 15 managers and 165 subordinates from a seafood processing plant in Thailand. The focus is on identifying and improving the interpersonal skill proficiencies of the managers in terms of self-awareness, listening, asking and coaching. Both self-evaluation and 360 degrees evaluation are employed in the surveys. The paper also reports quantitatively the changes in the subordinates’ role commitment. The post ODI result concludes that there is no statistically significant change in the interpersonal skills of the targeted mid-level managers. However, the outcome is at a developmental stage and initial findings advocate that positive change is in effect. Interview analysis and the descriptive statistics illustrate a trend towards increased utilization of their interpersonal skills in all areas. Correlation analysis demonstrates a moderately strong link between the managers’ self-evaluated coaching skills and subordinate’s role commitment. The role commitment of subordinates showed a positive change that was statistically significant. Although the research is completed on a tight time frame and is based on a family business, it demonstrates intriguing results applicable to any organizations that experiences rapid expansion. Also, it has implications for organizational communication research, particularly with respect to understanding of employee role commitment. ODI Studies exploring interpersonal skills managers and its effects on employees are available but very few in the Asian context, especially considering Thailand. The paper contributes greatly to the much needed understanding of such theme in the labor intensive seafood processing industries of Asia. Keywords: Interpersonal skills, self-awareness, listening, asking, coaching, role commitment